Real-time information sharing, customer orientation, and the exploration of intra-service industry differences : Malaysia as an emerging market - Ghouri, Arsalan Mujahid; Akhtar, Pervaiz; Haq, Mirza A.; Mani, Venkatesh; Arsenyan, Gayane; Meyer, Martin (Elsevier, 2021)
Differences in business practices and preferences are vital for understanding specific industries, particularly in relation to downstream operations in emerging markets. This study explores the effects of real-time information sharing (RTIS) on downstream operations in three service sub-sectors that are dominated by small and medium-sized enterprises (SMEs) - wholesale & retail, food & beverages, and accommodation. Drawing on information processing theory, we examine the differences in the adoption and perceived benefits for customers of RTIS through a survey of 221 middle-level managers from Malaysia. Our findings indicate that, overall, RTIS is significantly associated with customer purchase behavior (PB) in the presence of customer orientation (CO) that plays a two-fold mediating role in purchase and repurchase behavior. Our results also point to sectoral differences. RTIS—with customer PB and post-purchase behavior in the presence of CO—is more effective in the wholesale & retail and food & beverages sub-sectors than in accommodation. The article concludes with a discussion of theoretical and practical implications.
Keywords: Real-time information sharing; Customer orientation and purchase and repurchase behavior; Service industry and industry 4.0; emerging markets; fi=Tuotantotalous|en=Industrial Management|